Introducción a la estructura ecológica principal del Distrito Capital y su región ambiental: Conceptos fundamentales, ordenamiento territorial e instrumentos jurídicos - Vargas Fonseca, Alan David; Borja Cuadros, Odilia Margarita; Cristiano Mendivelso, Julián Felipe (Editorial Grupo AEA, 2024)
The Capital District, as a territorial entity located in the center of the Bogota Savanna, has the political and administrative responsibility to lead environmental sustainability and articulate with the Corporación Autónoma Regional de Cundinamarca (CAR) in order to preserve the ecological structure of the territory and promote sustainable land uses (urban and rural). To this end, there is a set of administrative tools and instruments contemplated in the Land Use Plan (POT) of the Capital District that all citizens should know and use to protect the ecosystems of the savanna of Bogota and the human rights associated with environmental sustainability. The objective of this publication is to contribute to the dissemination of these tools, through conceptualization and synthesis of relevant legal information on the subject. To achieve this purpose, this book is structured in two parts, the first one presents a theoretical contextualization and history of land use planning in Bogota and the second part presents the main concepts of the main ecological structure following the articles of the POT of Bogota - District Decree 555 of 2021.